Hubungan Infeksi HIV Pada Ibu hamil dengan Persalinan Prematur di RSD Dr. Soebandi Jember - Muhammad Ali Shodikin; Eva Deswinta Maharani; Yuli Hermansyah (Faculty of Medicine, Universitas Andalas, 2022)
Human Immunodeficiency Virus (HIV) infectionin pregnant women was increasing in Indonesia. HIV infection will lead complication risk to the mother and their babies. Objective: This study aims to determine the association of HIV infection in pregnant women and preterm birthat RSD Dr. Soebandi Jember.Method:An analytics descriptive with retrospective approach study was conducted. The subjects were medical records of HIV-positive pregnant women group and HIV-negative pregnant women group at RSD Dr. Soebandi Jember from August 2014 to July 2017. Result:Each of groups had 52 samples. In the HIV-positive pregnant women group, there were 19 preterm and 33 aterm birth, on the other hand, in the HIV-negative pregnant women group, there were 15 preterm and 37 aterm birth. The Chi Square test analysis was obtained p value = 0.403 (OR = 1.42). Conclusion: There was no significant correlation between HIV infection in pregnant women and preterm birth.